An Exploratory Study of Dogmatism and Its Relation to Group Response - Talley, William M.; Vamos, Peter (Canadian Journal of Counselling and Psychotherapy, 2012)
This is an exploratory study to determine the relationship of dogmatism and the concerns of group members. Subjects were administered the Rokeach Dogmatism Scale, Form E, and results tabulated by code. Each subject thereafter wrote an unstructured paragraph at the end of each group session about his feelings. These were similarly coded and, after they were analyzed and categorized, were matched with the dogmatism scores, It was found that those ranking high on the dogmatism scale were concerned to a significantly greater degree about the physical setting, the organization and structure of the group sessions, the topics discussed, the goals of the group, evaluation, and level of satisfaction with the group than were those scoring low on the dogmatism scale.